2022
DOI: 10.3390/nu14173454
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Vitamins and Trace Elements Losses during On-Line Hemodiafiltration

Abstract: Maintenance hemodialysis induces water-soluble vitamins and trace elements losses, which is why recommendations regarding potential supplementation were provided, but mainly based on conventional hemodialysis. This study′s aim was to measure the water–soluble vitamins and trace element losses during one on-line post-dilution hemodiafiltration (HDF) session. Thirty-nine patients under maintenance HDF were enrolled. We used the Theraflux® sampler (Theradial Corp., Orvault, France) to analyze the full session dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The first article about vitamins and minerals lost during HD was published in the 1980s [ 23 ]. Another study found important losses of water-soluble vitamins (B 1 , B 6 , B 9 , and C) during a standard 4 h hemodiafiltration session [ 24 ]. Schwotzer et al found that the levels of most vitamins are above the normal range in patients on hemodiafiltration receiving a classic dose of vitamin supplements, vitamin C excepted [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The first article about vitamins and minerals lost during HD was published in the 1980s [ 23 ]. Another study found important losses of water-soluble vitamins (B 1 , B 6 , B 9 , and C) during a standard 4 h hemodiafiltration session [ 24 ]. Schwotzer et al found that the levels of most vitamins are above the normal range in patients on hemodiafiltration receiving a classic dose of vitamin supplements, vitamin C excepted [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiamine stores are low and the use of an improperly balanced diet for several weeks can lead to its deficiency, especially in the case of HD patients, because the hemodialysis procedure causes the loss of this vitamin. The loss of vitamin B 1 during dialysis depends on the duration of the procedure and the type of hemodialysis used [ 6 , 24 ]. Jankowska et al measured that thiamine diphosphate (TDP), a bioactive compound of vitamin B 1 , is substantially lost during the HD procedure, and the amount of its loss is associated with body weight.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations